Variation in DVM behaviour of juvenile and adult pearlside (Maurolicus muelleri) linked to feeding strategies and related predation risk. (20th December 2012) - Staby, Arved; Srisomwong, Jantra; Rosland, Rune
Abstract In the Norwegian fjord Masfjorden, different developmental stages of the mesopelagic planktivore Maurolicus muelleri form vertically separate sound scattering layers (SSLs) and in late autumn display different diel vertical migration (DVM) behaviour. Post‐larvae and juvenile fish perform normal crepuscular DVM, whereas the large majority of adults remain at depth throughout the diel period. In this study we examined the stomach contents of juvenile and adult fish caught at different times and depths during a 24‐h period in autumn. The different DVM behaviour of these two SSLs in addition to a shallow layer believed to be composed of post‐larvae is explained with a model for visual foraging in aquatic environments that uses gradients in vertical light intensity and copepod density and size as input variables. Field data revealed that vertically migrating juveniles distributed at a higher ambient light intensity and on average consumed 25 times more copepods than non‐migrating adult fish. The model showed that juveniles experienced a 15 times higher prey encounter rate and a higher level of predation risk than non‐migrating adults, and that the energetic benefits for post larvae and juveniles from prolonged feeding in a nearly constant and brighter environment outweigh the associated predation risk. The model also suggests that the visual detection range of piscivore predators is relatively more limited by the turbid surface water than that of their prey, which provide the post‐larva and juvenile life‐stages of M. muelleri a window of reduced visual predation near the surface.